1996
DOI: 10.1126/science.272.5262.728
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Vascular Dysfunctions in Diabetic Rats by an Oral PKC β Inhibitor

Abstract: The vascular complications of diabetes mellitus have been correlated with enhanced activation of protein kinase C (PKC). LY333531, a specific inhibitor of the beta isoform of PKC, was synthesized and was shown to be a competitive reversible inhibitor of PKC beta 1 and beta 2, with a half-maximal inhibitory constant of approximately 5 nM; this value was one-fiftieth of that for other PKC isoenzymes and one-thousandth of that for non-PKC kinases. When administered orally, LY333531 ameliorated the glomerular filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
545
2
12

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,045 publications
(580 citation statements)
references
References 31 publications
21
545
2
12
Order By: Relevance
“…We used tumor mast cells (rat basophilic leukemia cells, RBL‐2H3; Kalesnikoff & Galli, 2008; Wollman & Meyer, 2012) which secrete only part (~30%) of their stored inflammatory agents in response to maximal antigen stimulation (Fig 1A), consistent with the existence of inhibitory pathways that prevent the release of the remaining vesicles. Since previous studies proposed that PKCB is the main PKC isoform regulating mast cell secretion (Nechushtan et al , 2000), we confirmed that inhibition of PKCB with ruboxistaurin (Ishii et al , 1996; Tsai et al , 2014) further reduces the amount of released vesicles in a dose‐dependent manner following stimulation with antigen (Fig 1A) or simultaneous addition of the PKC activators phorbol ester and Ca 2+ ionophore (Fig EV1A).…”
Section: Resultssupporting
confidence: 83%
“…We used tumor mast cells (rat basophilic leukemia cells, RBL‐2H3; Kalesnikoff & Galli, 2008; Wollman & Meyer, 2012) which secrete only part (~30%) of their stored inflammatory agents in response to maximal antigen stimulation (Fig 1A), consistent with the existence of inhibitory pathways that prevent the release of the remaining vesicles. Since previous studies proposed that PKCB is the main PKC isoform regulating mast cell secretion (Nechushtan et al , 2000), we confirmed that inhibition of PKCB with ruboxistaurin (Ishii et al , 1996; Tsai et al , 2014) further reduces the amount of released vesicles in a dose‐dependent manner following stimulation with antigen (Fig 1A) or simultaneous addition of the PKC activators phorbol ester and Ca 2+ ionophore (Fig EV1A).…”
Section: Resultssupporting
confidence: 83%
“…Adverse effects of elevated glucose levels on acetylcholine-induced relaxation of rabbit aorta and rat pial arterioles were restored by the addition of PKC inhibitors (Mayhan and Patel, 1995;Tesfamariam et al, 1991). These in vitro observations are supported by studies, demonstrating, that in vivo treatment with PKC inhibitors ameliorates vascular complications in diabetic rats (Ishii et al, 1996). Of course signal transduction and intracellular crosstalk by PKC dependent phosphorylation is manifold and complicated.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that treatment of DM rats with an endothelin type A receptor antagonist (BQ123), a PKCβ inhibitor (LY333531), or vitamin E could also ameliorate RBF abnormalities [10,27,30,31]. In addition, intravitreal injections of endothelin-1 or phorbol dibutyrate (an activator of PKC) rapidly induced retinal arteriole constriction and prolonged MCT, which mimicked diabetes [31,32].…”
Section: Discussionmentioning
confidence: 99%